Latvian Ethnography in Modern Clothing - Teilāne, Arta (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
Ethnography has long been one of the lasting fashion trends and it is a good foundation for the promotion of Latvian cultural heritage not only for foreign visitors but also for the Latvian population. Currently, one of the problems in the market is that mass products are available that are not interesting to consumers. Another problem is that designer clothes are mostly expensive and are unsuitable to be worn on a daily basis. The aim of this work is to create ethnographic, everyday clothes, based on ethnographic construction, correcting some defects that can prevent modern construction methodology. The present study has shown that it is possible to create a relevant, fashion trending clothes, while also promoting Latvian cultural heritage. Colors, patterns that are developed in different techniques, metal and woven details should be shown in clothing. This will not only boost patriotism among the Latvian population, but also developed the Latvian economy and create competition in the market. The study shows two examples of costume, where ethnographic construction were used and modified for requirements of modern clothing construction.